MEASURING THE EFFICIENCY OF HEALTH SYSTEM IN SUDAN USING DATA ENVELOPMENT ANALYSIS (DEA) - Omer Ali Eltahir; Nizar Ben Abdallah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
One of the central engrossments of the health sector is Efficiency. Objectives of the study to measure the efficiency of the health system in Sudan and to apply Data Envelopment Analysis (DEA) in studying the efficiency of the health system in Sudan. Two outputs and two inputs are the variables of this study; Outputs include life expectancy at birth, infant mortality rate. Inputs of this study include current health expenditure (% of GDP) and hospital beds. The most important result that health expenditure, (% of GDP), impact significantly the efficiency of the Sudan health system. The overall efficiency of the health system in Sudan is inefficient, with only3 years (2001, 2002, and2010) as efficient over the 19 years, with an efficiency average of 0.954. The study presents some recommendations such as direct to conduct a study on measuring Sudan's health system performance using more indicators.